Severe Vulvar Myiasis Case In A Crossbreed Limousin Cow - Anindya Sekar Putri Utami; Shelly Kusumarini Ramadhany; Taufik Mukti; Reza Yesica; Ajeng Erika Prihastuti Haskito (Journal of Applied Veterinary Science And Technology, 2024)
Background: Myiasis is caused by the infestation of Diptera fly larvae in vertebrate animals. In cases of myiasis, larvae will eat living or dead tissue, thereby expanding the infestation and infection of the host. Myiasis is a significant economic problem due to decreased productivity and tissue damage. Purpose: This study seeks to provide insights regarding managing and treating myiasis cases in cattle. Cases(s):  The 4-year-old female Limousin cow was in the gestation period and kept in Buluagung Village, Pesanggaran, Banyuwangi. Based on the owner's statement, the cow experienced a decrease in appetite, and there were wounds in the vulva area accompanied by larvae, which had been present for five days. The clinical findings revealed an open wound that was red in color and soft in consistency, and there was an unpleasant odor in the vulva area. An infestation of Diptera fly larvae accompanied this. After the initial extraction of maggots, necrotic tissue, edema, friable tissue, and erythema were evident in the vulvar region and introitus. Case Management:  Treatment carried out on the case cow involved cleaning the wound using 0.9% NaCl and removing both necrotic tissue and any larvae from the vulva wound using tweezers. The cow received an intramuscular injection of an analgesic and antipyretic (Sulprodon®) 7 mL, antihistamine (Prodryl®) 3 mL intramuscular injection, antibiotic (Limoxin-LA®) 10 mL, and multivitamin (Injectamin®) 7 mL. Conclusion:  The vulvar myiasis in this cow was successfully cured with no more larvae found, and the wound dried out.